Prevalence of intestinal parasites in newly diagnosed HIV/AIDS patients in Ilorin, Nigeria (2017)
Background: Human immune-deficiency virus/acquired immune-deficiency syndrome predisposes to opportunistic parasitic infestations of the gastrointestinal tract. This study aimed to determine the prevalence of intestinal parasites in newly diagnosed treatment naı¨ve HIV/AIDS patients. Methods: This hospital-based cross-sectional study was carried out from December 2010 to June 2011. Questionnaires were administered to 238 HIV/AIDS subjects, and 238 age and sexmatched controls. CD4+ T cell count was carried out on HIV-positive subjects. Stool samples were examined using direct microscopic and modified Ziehl-Neelsen methods. Positivity of intestinal parasites was taken as the presence of worms, oocyst, cyst, ova or larvae in the stool samples. Results: Ninety males and 148 females were studied for the HIV-positive and HIV-negative controls respectively. Intestinal parasitic infestation in HIV-positive subjects was 68.5%, and was significantly higher than in the HIV-negative controls 49.2% (P < 0.05). In HIV-positive subjects, Cryptosporidium spp. was the commonest (55.0%) parasite isolated. Others were Cyclospora cayetanensis (41.2%), Isospora belli (3.0%), Entamoeba histolytica (8.4%), Giardia lamblia (3.7%), Ascaris lumbricoides (2.5%), Strongyloides stercoralis (1.7%), Trichuris trichiura (0.8%) and Schistosoma mansoni (0.4%). HIV-positive patients with CD4+ T cell count of less than 200 cells/ul were more at risk of opportunistic parasites compared to the HIV-negative controls. Conclusion: The prevalence of intestinal parasites in newly diagnosed HIV/AIDS individuals was high, and its association with CD4+ T cell count was demonstrated. Routine screening for parasitic infestations at diagnosis is indicated to reduce the burden of the disease.